Hydropower development priority using MCDM method - Thanaporn Supriyasilp (2018)
Hydropower is recognized as a renewable and clean energy sources and its potential should be realized in an environmentally sustainable and socially equitable manner. Traditionally, the decision criteria when analyzing hydropower projects, have been mostly a technical and economical analysis which focused on the production of electricity. However, environmental awareness and sensitivity to locally affected people should also be considered. Multi-criteria decision analysis has been applied to study the potential to develop hydropower projects with electric power greater than 100 kW in the Ping River Basin, Thailand, and to determine the advantages and disadvantages of the projects in five main criteria: electricity generation, engineering and economics, socio-economics, environment, and stakeholder involvement. There are 64 potential sites in the study area. Criteria weights have been discussed and assigned by expert groups for each main criteria and subcriteria. As a consequence of weight assignment, the environmental aspect is the most important aspect in the view of the experts. Two scenarios using expert weight and fair weight have been studied to determine the priority for development of each project. This study has been done to assist policy making for hydropower development in the Ping River Basin. © 2009 Elsevier Ltd. All rights reserved.